Taxation as a tool to reduce inequality. (Journal of Economic Research & Business Administration, 2015)
The article deals with the problem of inequality in income distribution in the country and the impact on his personal income tax on individuals. Particular attention is paid to the study of scientific literature Russian authors on the subject, the definition and study from a scientific point of view the problem raised.